2014
DOI: 10.1088/0031-8949/89/10/105001
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic resonance in a discrete neuron with time delay and two different modulation signals

Abstract: Stochastic resonance in an excitable neuron based on the Rulkov map with noise, delay feedback, low-frequency signal and high-frequency signal is investigated numerically. The results show that there exist an optimal noise intensity, optimal time delay and optimal amplitude of the high-frequency signal at which the phase synchronisation between the low-frequency input signal and the output signal is the best. The Fourier coefficient is calculated to measure the stochastic resonance. It is found that the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…[37] Other similar studies on single neurons with time delay can be found in Refs. [38][39][40]. While for neural network constructed with multiple neurons, time delay plays a subtle role in either promoting or impeding synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Other similar studies on single neurons with time delay can be found in Refs. [38][39][40]. While for neural network constructed with multiple neurons, time delay plays a subtle role in either promoting or impeding synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…They have showed that presence of delay in the system exhibits more complicated dynamics than the non-delayed one. The effects of time delay on stochastic system have been investigated by many researchers [12][13][14][15]. More recently, the influences of time delay in stochastic insect outbreak model has been investigated [16].…”
Section: Introductionmentioning
confidence: 99%
“…Time delay is an important factor affecting the dynamical behavior of the systems, and even makes the system unstable. Therefore, the dynamical behavior of time-delayed systems has attracted considerable attention in various fields [26][27][28][29][30]. Time-delayed chaotic systems have more complex and abundant dynamics and are more suitable for some engineering applications, such as secure communication [31][32][33].…”
Section: Introductionmentioning
confidence: 99%